Debt, common mental disorders and mental health service use. (2nd November 2018) - Gunasinghe, Cerisse; Gazard, Billy; Aschan, Lisa; MacCrimmon, Shirlee; Hotopf, Matthew; Hatch, Stephani L.
Abstract: Background : Uncertainty remains as to whether the effects of debt on common mental disorder (CMD) are persistent over time and what impact it has on mental health service use (MHSU). Aims : To determine the distribution of debt across sociodemographic and socioeconomic statuses; to examine whether debt influences CMD recovery over time; and to determine the effects of episodic and/or long-term debt and CMD on MHSU outcomes. Methods : Data were collected from phase 1 ( N = 1698) and phase 2 ( N = 1052) of the South East London Community Health (SELCoH) study, a population-based survey. Results : 37.2% of participants who reported debt at SELCoH 1 and 46.6% at SELCoH 2 experienced concurrent CMD. Those with concurrent exposure to debt and CMD at SELCoH 1 were at greater risk of CMD at SELCoH 2. Debt accumulation was strongly associated with CMD cross-sectionally; however, this somewhat dissipated over time. Reporting any debt at SELCoH 2 or debt at both time-points were strongly associated with MHSU in the past year in the fully adjusted model adjusting for prior mental health. Conclusions : More focus is needed on concurrent exposure to debt and CMD with regards to subsequent psychological impact and consequences for MHSU.